2015
DOI: 10.1155/2015/428286
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Elastomeric Impression Materials: An In Vitro Comparison

Abstract: Purpose. Although new elastomeric impression materials have been introduced into the market, there are still insufficient data about their mechanical features. The tensile properties of 17 hydrophilic impression materials with different consistencies were compared. Materials and Methods. 12 vinylpolysiloxane, 2 polyether, and 3 hybrid vinylpolyether silicone-based impression materials were tested. For each material, 10 dumbbell-shaped specimens were fabricated (n = 10), according to the ISO 37:2005 specificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…The alternative hypothesis demonstrated that the presence of the tags was statistically significant in the samples under examination, and therefore relevant from the clinical point of view. It is now known that the interface area between the impression material and the tooth is the most complex to manage due to the potential for elastic deformation during removal [38]. For this reason, the characteristics of the elastic deformation during the phase of removal of the impression are among the most studied rheological characteristics of impression materials [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The alternative hypothesis demonstrated that the presence of the tags was statistically significant in the samples under examination, and therefore relevant from the clinical point of view. It is now known that the interface area between the impression material and the tooth is the most complex to manage due to the potential for elastic deformation during removal [38]. For this reason, the characteristics of the elastic deformation during the phase of removal of the impression are among the most studied rheological characteristics of impression materials [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Addition silicones also have additional properties, such as very high elastic recovery and high tear and tensile strengths 11. The laboratory study by Re et al has proven that addition silicones have shown higher in vitro results for tensile strength at break and yield strength 12. Hence, with the support of the ideal mechanical properties of addition silicones, the authors have used only the addition silicone material for the construction of the vaginal dilator to maintain the adequate patency of the neovagina in the present case report.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the mould was opened, and the test specimens were removed from the mould. Re et al5 indicated that there were significant effects of the waiting period on both viscosity and mechanical properties of the alginate impression materials. Therefore, all tests were conducted after enough setting times.…”
Section: Methodsmentioning
confidence: 99%
“…While alginate impression materials indicate high mechanical properties to ensure their stability during dental treatments,5 alginate impression materials are required to have enough viscosity to make a way into all oral structures. There are various mechanical tests applied to impression materials and their mechanical properties, such as ANSI/ADA specification no.…”
Section: Introductionmentioning
confidence: 99%